2006
DOI: 10.1007/s00335-006-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the melanocortin-4 receptor cause variable obesity in mice

Abstract: Mutations in the melanocortin-4 receptor (MC4R) are associated with early-onset obesity in humans. Furthermore, a null Mc4r allele in mice leads to severe obesity due to hyperphagia and decreased energy expenditure. As part of independent N-ethyl- N-nitrosourea (ENU) mutagenesis screens, two obesity mutants, Fatboy and Southbeach, were isolated. Mapping revealed linkage to the melanocortin-4 receptor (Mc4r) and sequencing found single amino acid changes in Mc4r for each line. Expression of the mutant receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The I269N substitution may change the packing of the extracellular ends of TM6 and TM5, and, thus, may affect the receptor stability, leading to misfolding and loss-of-function. This mechanism is supported by a recent observation that the I194T mutation of a contacting residue from TM5 caused impaired MC4R expression and signaling and an obese phenotype in mice (28). The presence of a polar residue in the lipid-exposed surface of TM6 may also alter the orientation of the whole receptor relative to the membrane plane that would affect protein-protein interaction in membranes.…”
Section: Models Of Mutants With Decreased Cell Surface Translocationmentioning
confidence: 75%
“…The I269N substitution may change the packing of the extracellular ends of TM6 and TM5, and, thus, may affect the receptor stability, leading to misfolding and loss-of-function. This mechanism is supported by a recent observation that the I194T mutation of a contacting residue from TM5 caused impaired MC4R expression and signaling and an obese phenotype in mice (28). The presence of a polar residue in the lipid-exposed surface of TM6 may also alter the orientation of the whole receptor relative to the membrane plane that would affect protein-protein interaction in membranes.…”
Section: Models Of Mutants With Decreased Cell Surface Translocationmentioning
confidence: 75%
“…The current trend indicated by several recent studies is to test any identified MC4R mutation for loss-of-function, although loss-offunction mutations in the MC4R do not necessarily lead to obesity as the penetrance of MC4R mutations in causing obesity is not 100% [30]. Nevertheless, it has been established that MSHs, signaling through Gs protein/adenylyl cyclase, activate MC4R, a critical component of the hypothalamic melanocortin system involved in energy homeostasis, leading investigators to deduce that mutations in MC4R could be responsible for monogenic obesity in humans [12,13] and mice [8,31]. MC4R loss-of-function can be characterized as decreased cell surface expression, decreased ligand binding, and/or disturbed receptor signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Only one report demonstrated a lower potency of orexigenic AGRP on V103I corresponding to the distribution of this allele in population screens [52]. Several point mutations in the Mc4r gene introduced by chemical mutagenesis have been shown to cause different severity of obesity in mice [40]. Mouse lines encoding certain point mutations of interest are required to elucidate the effects of certain alleles on metabolism in vivo.…”
Section: Mouse Models For the Analysis Of Gene Variantsmentioning
confidence: 99%